Optimization of Polyvinyl Alcohol (PVA) and Xanthan Gum Edible Film (Crocus sativus L.) as Antibacterial against Staphylococcus aureus - Prihandi Surya Samudra; Lilies Wahyu Ariani; Intan Martha Cahyani (Journal of Food and Pharmaceutical Sciences, 2022)
Staphylococcus aureus is a normal bacteria flora in the oral cavity and often causes infections. Saffron (Crocus sativus L.) contains flavonoids that can inhibit the growth of Staphylococcus aureus. Saffron extract is formulated into edible film preparations because it can control drug release and maintain active substances, especially antibacterial ones. This study aims to determine the effect of comparing PVA and xanthan gum concentrations on edible film preparation physical characteristics and antibacterial activity. Also, to find out the optimal formula. This study uses the Simplex Lattice Design method and Design Expert to determine the concentration ratio. The optimization parameters of the preparation included pH, soluble time, water absorption, and antibacterial activity test using the well diffusion method. The ANOVA results showed that adding PVA concentration accelerated the dissolution time and increased the antibacterial inhibition. The addition of xanthan gum concentration increased the pH value and water absorption. The test results obtained pH 5.52, dissolution time 22.25 seconds, water absorption capacity is 43.95%, and antibacterial inhibition is 0.53 cm. The optimal formula was received at the concentration of PVA at 5.59% and xanthan gum at 0.41%. T-test shows that the equation of each optimal parameter is valid.